Stakeholder democracy
1 online resource
Keywords: In the context of sustainable development, this book describes how we are moving from representative to participatory democracy, and how we are now in a "stakeholder democracy," which is working to strengthen represented democracy in a time of fear. Since the 1992 Rio Earth Summit the idea of stakeholder democracy has grown, with stakeholders engaged in helping governments and intergovernmental bodies make better decisions, and in helping them to deliver those decisions in partnerships amongst various stakeholders, with and without government. Seen through a multi-stakeholder, sector and level lens, this book describes the history of the development of stakeholder democracy, particularly in the area of sustainable development. The authors draw on more than twenty-five years of experience to review, learn from and make recommendations on how best to engage stakeholders in policy development. The book illustrates successful practical examples of multi-stakeholder partnerships (MSPs) to implement agreements and outline elements of an MSP Charter. This will provide a benchmark for partnerships, enabling those being developed to understand what the necessary quality standards are and to understand what is expected in terms of transparency, accountability, financial reporting, impact and governance. The book is essential reading for professionals and trainees engaging in multi-stakeholder processes for policy development and to implement agreements. It will also be useful for students of sustainable development, politics and international relations.